A razão cintura para estatura relacionada ao perfil gligêmico elevado em meninos - Smolarek, André de Camargo (2012)
To verify the association of anthropometric indicators with risk factors for cardiometabolic diseases is extremely important especially in adolescents. The aim of this study was to investigate the association of waist height ratio (WHratio) with the glucose profile (GL) in boys of the town of Curitiba, Brazil the sample consisted of 123 boys from 14.25 ± 2.25 years old. Was measured weight, height, waist circumference, fasting GL, WHratio. The statistics used were mean, standard deviation and frequency percentile, Pearson correlation and binary logistic regression CI-95% and p